2021
DOI: 10.1200/jco.2021.39.3_suppl.217
|View full text |Cite
|
Sign up to set email alerts
|

Results of a phase II trial of ramucirumab plus irinotecan as second-line treatment for patients with advanced gastric cancer (HGCSG 1603).

Abstract: 217 Background: Ramucirumab (RAM) is a fully human IgG1 monoclonal vascular endothelial growth factor receptor-2 (VEGFR-2) antibody. The RAINBOW trial showed RAM plus paclitaxel (PTX) increased overall survival (OS) compared with PTX alone for advanced gastric cancer (AGC) in second-line treatment. WJOG 4007 trial demonstrated equivalent efficacy between irinotecan (IRI) and PTX. We conducted this trial to examine the efficacy and safety of RAM plus IRI combination therapy in the second-line treatment for AGC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Комбинация рамуцирумаба с иринотеканом во 2-й линии лечения при дРЖ, апробированная в Японии [26], не достигла главной цели исследования, оказавшись недостаточно эффективной.…”
Section: Discussionunclassified
“…Комбинация рамуцирумаба с иринотеканом во 2-й линии лечения при дРЖ, апробированная в Японии [26], не достигла главной цели исследования, оказавшись недостаточно эффективной.…”
Section: Discussionunclassified
“…The combined therapy with ramucirumab and irinotecan demonstrated acceptable safety profile, with no emergence of new or unexpected adverse effects observed in the trial. According to phase II trial investigating the clinical efficiency of ramucirumab plus irinotecan as second-line treatment, median PFS and OS were 4.2 months (95% CI 2.5-5.4 months) and 9.6 months (95% CI 6.4-16.6 months), respectively [30]. The results are similar to that of RIND-BeRG trial, which is in third-or later-line setting, suggesting the efficacy of this regimen even in salvage-line treatment.…”
Section: Irinotecanmentioning
confidence: 99%
“…A previous study demonstrated that the combination of bevacizumab, an anti-VEGF antibody, with irinotecan and 5-FU has significant antitumor activity in metastatic colorectal cancer ( 37 ). Recently, a phase II trial of ramucirumab plus irinotecan has shown encouraging results as second-line therapy in gastric cancer ( 38 ).…”
Section: Introductionmentioning
confidence: 99%